MOTIF RASIONAL KEPUTUSAN NASABAH MEMILIH PRODUK TABUNGAN EMAS DI PT. PEGADAIAN (PERSERO), Tbk. CABANG SUMBAWA BESAR - Sutanty, Marisa; Azurawati, Kiki (Fakultas Ekonomi dan Manajemen, 2025)
This study aims to know the effect of rational motives on customers' decisions to choose gold savings products at PT. Pegadaian (Persero), Tbk. branch of Sumbawa Besar. The type of this study was associative study which aims to examine the effect of rational motives (X) on customers' decisions to choose gold savings products at PT. Pegadaian (Persero), Tbk. branch of Sumbawa Besar (Y). The type of data used in this study was quantitative obtained directly from primary sources using a research instrument in the form of a questionnaire. The respondents in this study were 67 gold savings product customers at PT. Pegadaian (Persero), Tbk., branch of Sumbawa Besar. Determination of respondents in this study used a probability sampling technique with the simple random sampling method. The data used in this study was processed using the SPSS application to be analyzed using simple linear regression analysis techniques, partial hypothesis testing (t-test), and coefficient of determination testing (R2). The results of this study showed that rational motives had a positive and significant effect on customers' decisions to choose gold savings products at PT. Pegadaian (Persero), Tbk. branch of Sumbawa Besar. The ability of rational motives to effect on customers' decisions to choose gold savings products at PT. Pegadaian (Persero), Tbk. branch of Sumbawa Besar was 80.8%, while the remaining of 19.2% was effected by other factors outside this research model, such as customer confidence in the product in question, confidence in references and customer past experiences.